KAITAN MAKNA KONTEKSTUAL DENGAN BUDAYA MINANGKABAU DALAM NOVEL PERSIDEN KARYA WISRAN HADI - Putri Dian Afrinda; Samsiarni Samsiarni (Jurnal Bahasa Lingua Scientia, 2018)
This study aims to identify contextual meanings that reflect the culture of the Minangkabau people found in Wisran Hadi's Persiden novel. This is so that readers can immediately get to know the culture of the Minangkabau people who are full of meaning. This type of research is qualitative using the content analysis approach. Data are classified based on their contextual meanings, and the final step is understanding the Minangkabau culture as a setting in Wisran Hadi's Persiden novel. The results of this study are as follows, first in Wisran Hadi's Persiden novel Contextual meaning when viewed from linguistic context, figurative language describes about the culture of Minangkabau people on average, from the emotional context used to evoke memories or emotional feelings towards change and memories of adat the tradition that began to shift, from the site context the author tried to present a turbulent situation in the life of Minangkabau people today, whereas from the cultural context it was shown that the author used terms that were very close to the life of the Minangkabau people, so that they could become cultural markers. Second, the relation of contextual meaning to the understanding of the culture of Minangkabau people in Wisiden Hadi's Persiden novel is found in many parables about the matrilineal system adopted by the Minangkabau people, one of which is the position of men in marriage. Wisran Hadi is like a reminder of the Minangkabau customs of the past, such as the function of Mamak and the position of Semenda.